Deskripsi Pemahaman Geometri Siswa Berdasarkan Level Van-Hiele Ditinjau dari Kecerdasan Spasial Siswa - Alif Nur Indriyani; Wanda Nugroho Yanuarto (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2020)
This study aims to describe the understanding of geometry based on the level of Van Hiele in terms of spatial intelligence in class X MA Al Hidayah 1 Purwareja Klampo. In the study divided into 3 groups: students who have high, low and medium spatial intelligence. The instruments used to collect data are tests, interviews, and documentation. The validation test used is technical triangulation, comparing the test results and the results of student interviews. The results of this study indicate that: 1) students who have high spatial intelligence are able to reach the level of the third level of van hiele (Understanding Deduction). 2) students who have spatial intelligence are able to reach the level of the second level van hiele (Informal Deduction). 3) students who have low spatial intelligence are able to reach evel van hiele stage 1 (Analysis).